How writers work : finding a process that works for you - Fletcher, Ralph J. (New York : HarperCollins, 2000)
Focuses on the skills and techniques necessary for good writing, with excerpts from established writers and samples of young people's work as examples.
Includes bibliographical references (p. 113-114).
3 4 13
Keywords: Authorship -- Juvenile literature; Authorship; Creative writing